Upaya pembentukan karakter disiplin siswa melalui pembiasaan dan keteladanan guru kelas V SDN 2 Bangbayang - Aulia Fitri; Nana Ganda; Elan (IKIP Siliwangi, 2024)
This study aims to determine the efforts to form disciplinary character through habituation and exemplary class V teachers at SDN 2 Bangbayang. Schools really need efforts to form this character because it will become the basis for implementing disciplinary character education for students. Given the time of the Covid-19 pandemic in Indonesia, more or less shifted the values and norms that students had. Character is the difference between one and the other because the character is character, nature, which is very basic in a person. The method in this study uses a descriptive qualitative design that tends to use an inductive approach. The objects of this research were the Class V teachers and students. Data collection techniques using observation, interviews, and documentation. For the data's validity use source, technical, and time triangulation. Then analyzed by means of data reduction, data presentation, and verification. The results of the study show that there are two ways of character building, namely, one with a deliberate demonstration; by direct displays of teacher discipline, responsibility, and concern for the environment, and then by occasional example; like a teacher who always says sorry, please, thank you, respect teachers, superiors, especially students. The exemplary and habituation carried out by the teacher to students goes well, so it can be said to be successful.